Outcomes and Complications Associated with Mechanical Thrombectomy in the Treatment of Acute Ischemic Stroke - Ahmed, Zubair; Pan, Jeremy; Eskandar, Tony; Agrawal, Devendra K. (Cardiology and Cardiovascular Medicine, 2024)
Universally, stroke presents as neurological deficits due to the obstruction of blood supply to specific regions of the brain. Among the three main categories of stroke, acute ischemic stroke is the leading cause of death and disability worldwide. As of today, there are two effective treatment methods: thrombolysis and endovascular therapy. Intravenous thrombolysis treatment via tissue plasminogen activator is typically administered within 4.5 hours from the onset of symptoms. Mechanical thrombectomy, a type of endovascular therapy, is indicated for acute ischemic stroke due to a large vessel occlusion occurring within 24 hours since the patient was last seen asymptomatic. Due to the disadvantages of intravenous thrombolysis treatment, such as a limited time window and numerous contraindications, studies have proven the efficacy of mechanical thrombectomy as the standard of care for acute ischemic stroke due to large vessel occlusion in the anterior circulation. Endovascular therapy was associated with higher rates of independent clinical outcome and successful reperfusion rates compared to intravenous thrombolysis treatment. Currently, stent retrievers and aspiration devices are the two most common endovascular therapy techniques. Two prominent studies compared the reperfusion rates between these two techniques, but neither was found to be more beneficial than the other. The decision to use either a stent retriever or direct aspiration depends on the patient and the thrombus involved. This comprehensive article critically discusses the findings on the efficacy of mechanical thrombectomy therapy for acute ischemic stroke and its associated outcomes and complications.